2016
DOI: 10.1016/j.indcrop.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Development of near-infrared spectroscopy calibrations to measure quality characteristics in intact Brassicaceae germplasm

Abstract: a b s t r a c tDetermining seed quality parameters is an integral part of cultivar improvement and germplasm screening. However, quality tests are often time consuming, seed destructive, and can require large seed samples. This study describes the development of near-infrared spectroscopy (NIRS) calibrations to measure moisture, oil, fatty acid profile, nitrogen, glucosinolate, and chlorophyll content in six species from the Brassicaceae family. Rapeseed and similar oilseeds are potential feedstocks for produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
1
8
2
Order By: Relevance
“…Our results agreed with and compared favorably to previously reported results. Our SEC (1.05%) was lower than the one obtained by Oblath et al () who reported an SEC of 3.1% for oleic acid with a sample range of 7.1–65.5%. In 1994, Daun et al reported an SEP values of 4.7% and 4.8% for an oleic acid range of 55.6–65.6% for a model obtained with 13 factors (R 2 val = 0.903 and 0.909, RPD = 2.54 and 2.62).…”
Section: Resultscontrasting
confidence: 87%
See 3 more Smart Citations
“…Our results agreed with and compared favorably to previously reported results. Our SEC (1.05%) was lower than the one obtained by Oblath et al () who reported an SEC of 3.1% for oleic acid with a sample range of 7.1–65.5%. In 1994, Daun et al reported an SEP values of 4.7% and 4.8% for an oleic acid range of 55.6–65.6% for a model obtained with 13 factors (R 2 val = 0.903 and 0.909, RPD = 2.54 and 2.62).…”
Section: Resultscontrasting
confidence: 87%
“…Daun et al () used 11 and 13 factors in their models with benchtop instruments for a total glucosinolates content range of 9.7–30 μmol/g ( B. napus and B. rapa) ; their SEP and R 2 val ranged from 1.7 to 3.8 μmol/g and 0.812 to 0.899, respectively, depending on the instrument model. Oblath et al () used various Brassica species with a much larger total glucosinolates range (5.5–117.4 μmol/g); their SEC of 8.19 μmol/g was higher than the one obtained with our handheld instrument. Petisco et al () used B. napus and B. carinata to develop a global total glucosinolates model (range 15.8–97.9 μmol/g) using only seven factors.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Additionally, the NIRS technique has been successfully applied in Brassica species to predict seed viability (Lee et al, ; Shrestha, Deleuran, & Gislum, ), seed vigour (Kandpal, Lohumi, Kim, Kang, & Cho, ) and seed germination (Al‐Amery et al, ), as well as the seed oil content (Tkachuk, ), fibre fractions (Font et al, ; Stubbs & Kennedy, ; Wittkop, Snowdon, & Wolfgang Friedt, ), protein content (Daun, Clear, & Williams, ), and glucosinolate (Velasco & Becker, ), and chlorophyll concentrations (Oblath et al, ). The NIRS calibration for estimating the tocopherol content in sunflower seeds (Gotor, Berger, et al, ), alfalfa (González‐Martín, Hernández‐Hierro, Bustamante‐Rangel, & Barros‐Ferreiro, ) and olive oil (Cayuela & García, ) have been reported.…”
Section: Introductionmentioning
confidence: 99%